Criteria of school quality from the view of the Czech School Inspection and Quality Management Systems ISO and CAF - Ilona Jirečková (Czech Pedagogical Society, 2011)
Criteria of school quality from the view of the Czech SchoolInspection and Quality Management Systems ISO and CAFAbstract: The article contributes to problems of quality management, specifically tocriteria of school quality. It informs about criteria given by the Czech School Inspectionas a traditional model in education and about criteria given by quality managementsystems ISO 9001 and CAF, which are being used in Czech education and also ininternational context. The aim is to clarify basic components within the frame of threepresented criterion models and to pay attention to their connections and differences.